Rise times of impulsive high-current processes in cloud-to-ground lightning. - Willett, J.C.
Measurements are presented of electric-field derivative (dE/dt) waveforms that were radiated by first and subsequent return strokes, stepped, and dart-stepped-leader steps just before return strokes and ?characteristic pulses? in normal (negative) cloud-to-ground lightning under conditions of minimal distortion due to ground-wave propagation. The main dE/dt peaks produced by the fast-rising portions of all of these processes are found to have similar durations [mean full-width at half-maximum (FWHM) ranging from 79±20 ns for subsequent strokes to 54±17 ns for stepped-leader steps], although widely differing absolute magnitudes (spanning nearly a factor of four). Field-change (E) signatures of first strokes are examined in greater detail after eliminating the 39% of events with multiple dE/dt peaks during their fast-rising portions. The ?slow fronts? beginning these waveforms had durations of 3.7±1.2 μs and amplitudes 50%±10% of peak E. The latter ratio was uncorrelated with either peak E or peak dE/dt. The range-normalized peak magnitudes of the remaining fast-rising portions of these field changes were well correlated with those of the corresponding dE/dt signatures, whereas the values of FWHM of dE/dt were uncorrelated with peak dE/dt and only poorly correlated with peak E
Keywords: Characteristic pulses; Cloud-to-ground lightning; Dart-stepped-leader steps; Electric-field derivative waveforms; Electric-field measurement; Field-change signatures; First strokes; Ground-wave propagation; Impulsive high-current processes; Mean full-width at half-maximum.; Minimal distortion; Range-normalized peak magnitudes; Return strokes; Rise times; Slow fronts; Stepped-leader steps